Growth, electronic and magnetic properties of doped ZnO epitaxial and nanocrystalline films - Chambers, S.A.; Schwartz, D.A.; Liu, W.K.; Kittilstved, K.R.; Gamelin, D.R. (Applied physics. A, Materials science & processing, 2007)
We have used oxygen plasma assisted metal organic chemical vapor deposition along with wet chemical synthesis and spin coating to prepare CoxZn1-xO and MnxZn1-xO epitaxial and nanoparticle films. Co(II) and Mn(II) substitute for Zn(II) in the wurtzite lattice in materials synthesized by both methods. Room-temperature ferromagnetism in epitaxial Co:ZnO films can be reversibly activated by diffusing in Zn, which occupies interstitial sites and makes the material n-type. O-capped Co:ZnO nanoparticles, which are paramagnetic as grown, become ferromagnetic upon being spin coated in air at elevated temperature. Likewise, spin-coated N-capped Mn:ZnO nanoparticle films also exhibit room-temperature ferromagnetism. However, the inverse systems, N-capped Co:ZnO and O-capped Mn:ZnO, are entirely paramagnetic when spin coated into films in the same way. Analysis of optical absorption spectra reveals that the resonances Co(I)↔Co(II)+e-CB and Mn(III)↔Mn(II)+h+VB are energetically favorable, consistent with strong hybridization of Co (Mn) with the conduction (valence) band of ZnO. In contrast, the resonances Mn(I)↔Mn(II)+e-CB and Co(III)↔Co(II)+h+VB are not energetically favorable. These results strongly suggest that the observed ferromagnetism in Co:ZnO (Mn:ZnO) is mediated by electrons (holes).